HIF-2α not HIF-1α overexpression confers poor prognosis in non–small cell lung cancer - Zhao-Jia Gao; Yong Wang; Wei-dong Yuan; Jun-qiang Yuan; Kai Yuan (Tumor Biology)
HIF-α may play an important role in the process of tumorigenesis as well as tumor progression. Although a number of investigations have established the significance of HIF-1α in several human tumors, there is still little information available on the clinical significance of HIF-2α expression in non-small cell lung cancer (NSCLC). In present study, immunohistologic expression of HIF-1α/ HIF-2α was studied in a tissue microarray of 140 Stage I-III NSCLCs and correlated with clinicopathologic parameters and clinical outcome. We found that HIF-1α/ HIF-2α showed a cytoplasmic pattern of expression in tumor cells while normal lung components showed negative or weak cytoplasmic staining. High HIF-1α and HIF-2α expression was noted in 49/140 (35.0%) and in 64/140 (45.7%) of the cases respectively. There was no direct correlation between HIF-1α and HIF-2α expression ( p  = 0.200). The high HIF-2α expression was associated with histology (squamous cell carcinoma vs. adenocarcinomas) in these patients ( p  = 0.001). Patients in advanced tumor stage had frequent high expression of HIF-2α ( p  = 0.007), and the similar high expression was also observed in advanced T or N stage ( p  = 0.030 and 0.043, respectively). HIF-1α showed a marginal association with T stage ( p  = 0.084), which showed a higher expression in early tumor stage. Univariate analysis of the overall survival demonstrates that HIF-2α expression but not HIF-1α was related to poor outcome ( p  = 0.005) and it retained significance in multivariate analysis ( p  = 0.046). In conclusion, HIF-2α expression was related to tumor size, lymph node metastasis, tumor stage and histology. We also found a positive prognostic value of HIF-2α protein expression. HIF-2α might serve as a potential prognosis biomarker in evaluating progression and prognosis of NSCLC. We believe that our study will be of great benefit to the clinical treatment and prognostic evaluation of NSCLC.